Manganese response and nutrient uptake in conventional and glyphosate-resistant soybean - Loecker, Jami L. (Kansas State University, 2008)
Glyphosate-resistant (GR) soybean cultivars are widely accepted in the United States. Glyphosate-resistance provides many benefits to production agriculture, yet GR soybeans may require some additional management practices. The objectives of this research are to (a) determine response of GR and conventional (CV) soybean near isoline to manganese fertilization, (b) determine nutrient concentration and uptake in GR and CV soybean, (c) determine differences in yield of GR and CV soybean varieties, (d) quantifying Mn uptake when glyphosate is and is not applied to glyphosate-resistant soybean, and (e) determine glyphosate effect on soybean response to Mn treatments. A field study was conducted at 5 locations in Kansas from 2006 through 2007. Manganese soil test levels ranged from 4 to 52 mg Mn/kg. Soybean (near isoline) varieties were planted at each location in a split-block design with 4 replications. Manganese treatments consisted of soil-applied MnSO[subscript]4 at 0, 2.8, 5.6, and 8.4 kg Mn/ha and foliar applied Mn at 0.22 and 0.45 kg Mn/ha. Leaf tissue and whole plant samples were taken at approximately R1, R3, and R6 growth stages and analyzed for N, P, K, Mn, and other nutrient concentrations. Few significant differences were found between varieties for concentration of any nutrient. Overall nutrient uptake under optimal growth conditions was greater in GR soybean than CV soybean varieties. There were no yield differences between GR and CV soybean varieties at low yielding locations (< 3.3 Mg/ha). In high yielding environments, CV soybean yield was greater than GR soybean yield for the 0 kg Mn/ha rate. However, granular Mn additions increased yield of GR soybean but did not affect CV soybean yield while foliar Mn treatments at high yielding locations increased yields in GR and CV soybean. In addition, a greenhouse study was conducted with a completely randomized block design having 5 blocks. Manganese treatments in the greenhouse study consisted of soil-applied MnSO[subscript]4 at 0, 8.5, 17, and 25.5 mg Mn/pot and foliar applications of 0.66 and 1.33 mg Mn/pot. Treatments were with and without glyphosate applications. Glyphosate applications did not alter Mn concentrations or total Mn uptake in the soybean biomass.
Keywords: soybean; manganese; glyphosate; Agriculture, Agronomy (0285)